Knee Dislocations and PCL-Based Multiligament Knee Injuries in Patients Aged 18 Years and Younger: Surgical Technique and Outcomes - Fanelli, Gregory C.; Fanelli, David G. (The Journal of Knee Surgery, 2016)
Knee dislocations and posterior cruciate ligament (PCL)–based multiple ligament knee injuries are complex injuries that can result in significant functional instability for the affected individual. The purpose of this article is to present a review of the literature, and the authors' experience treating knee dislocations and PCL-based multiple ligament knee injuries in patients 18 years of age and younger. This article will discuss patient age at the time of surgery, mechanisms of injury, surgical techniques, considerations in patients with open growth plates, a review of the literature, and the authors' surgical outcomes in these complex knee ligament instabilities.
Keywords: knee dislocation; allograft; mechanical graft tensioning; multiple ligament knee injury; adolescent; open growth plates; posterior cruciate ligament